Improving asthma self-management education through inhaler labeling - Lea C. Dikranian; D. Elizabeth Irish; Kathleen E. Shanley; Don R. Walker; Stephen K. de Waal Malefyt (PEC Innovation)
Objective: Improper use and poor understanding of asthma medications can lead to poorly controlled asthma, emergency department visits, and hospitalizations for children with asthma. Pharmacists play a critical role in improving asthma medication adherence through education on asthma self-management. The use of color-coded labels applied at pharmacies to help patients differentiate between rescue and maintenance inhalers has not been explored. Methods: Pharmacies were recruited to join a community pharmacy asthma coalition. Pharmacists provided patient education and labeled inhalers with two types of color-coded stickers. A red sticker labeled “RESCUE” was used for short-acting β-2 agonist medication inhalers. A green sticker labeled “USE EVERY DAY” was used for inhaled corticosteroids (ICS) or combination ICS/long-acting β-2 agonist medication inhalers. Results: During the two years of the pilot program, 25 pharmacy locations participated. Pharmacies labeled over 6000 rescue and 9000 controller medications using color-coded labels. Over 1000 children and 7000 adults were served by the coalition. Conclusion: Color-coded asthma medication labels can be successfully utilized by pharmacies. This low-cost tool provides vital information regarding the proper use of asthma medications. Innovation: The color-coded labeling of asthma medications is a novel innovation that can be successfully used by pharmacists to improve asthma self-management education.